Mapping Chemical Elements and Iron Oxidation States in the Substantia Nigra of 6-Hydroxydopamine Lesioned Rats Using Correlative Immunohistochemistry With Proton and Synchrotron Micro-Analysis - Carmona, Asuncion; Roudeau, Stéphane; Perrin, Laura; Carcenac, Carole; Vantelon, Delphine; Savasta, Marc; Ortega, Richard (Frontiers in Neuroscience, 2019)
Brain metal homeostasis is altered in neurodegenerative diseases and the concentration, the localization and/or the chemical speciation of the elements can be modified compared to healthy individuals. These changes are often specific to the brain region affected by the neurodegenerative process. For example, iron concentration is increased in the substantia nigra (SN) of Parkinson’s disease patients and iron redox reactions might be involved in the pathogenesis. The identification of the molecular basis behind metal dyshomeostasis in specific brain regions is the subject of intensive research and chemical element imaging methods are particularly useful to address this issue. Among the imaging modalities available, Synchrotron X-ray fluorescence (SXRF) and particle induced X-ray emission (PIXE) using focused micro-beams can inform about the quantitative distribution of metals in specific brain regions. Micro-X-ray absorption near edge spectroscopy (XANES) can in addition identify the chemical species of the elements, in particular their oxidation state. However, in order to bring accurate information about metal changes in specific brain areas, these chemical imaging methods must be correlated to brain tissue histology. We present a methodology to perform chemical element quantitative mapping and speciation on well-identified brain regions using correlative immunohistochemistry. We applied this methodology to the study of an animal model of Parkinson’s disease, the 6-hydroxydopamine (6-OHDA) lesioned rat. Tyrosine hydroxylase immunohistochemical staining enabled to identify the SN pars compacta (SNpc) and pars reticulata (SNpr) as well as the ventral tegmental area (VTA). Using PIXE we found that iron content was higher respectively in the SNpr > SNpc > VTA, but was not statistically significantly modified by 6-OHDA treatment. In addition, micro-SXRF revealed the higher manganese content in the SNpc compared to the SNpr. Using micro-XANES we identified Fe oxidation states in the SNpr and SNpc showing a spectral similarity comparable to ferritin for all brain regions and exposure conditions. This study illustrates the capability to correlate immunohistochemistry and chemical element imaging at the brain region level and this protocol can now be widely applied to other studies of metal dyshomeostasis in neurology.